Use of electronic apex locator in the impossibility of radiographic visualization of the root apex: report of two cases - Ricardo Machado; Luiz Fernando Tomazinho; Ângela Mayara Azedo Stel; Emmanuel João Nogueira Leal Silva; Luiz Pascoal Vansan (Revista Sul-Brasileira de Odontologia, 2014)
Electronic apex locators have been widely used for foraminal identification and for working length determination. The establishment of a correct apical limit is essential for a good prognosis in cases of pulp vitality or pulp infection. Objective and Case reports: The aim of the study is to report two cases where the use of electronic apex locators was crucial due to the inability to visualize the root apex due to a post-surgical retaining plate (case 1) and during orthodontic treatment with a maxillary expander (case 2). Conclusion: In this light we could confirm the effectiveness of these devices for the determination of the working length when it is impossible to perform it by radiographic techniques.